2006
DOI: 10.1094/pd-90-0592
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Response to Flooded Soil Conditions and the Association with Soilborne Plant Pathogenic Genera

Abstract: The role of soilborne pathogens in flood damage on soybeans, Glycine max, was examined using six genotypes representing a reputed range of flood tolerances. Genotypes were planted in single-row plots from 1996 to 1998 with flood treatments of no flood, flood at emergence (3-day duration), or flood at the fourth leaf node growth stage (7-day duration). Three or four days after removing each flood treatment, plant stands were estimated and 15 plants were collected from each plot, weighed, and rated for root disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…helicoides, have been isolated from diseased soybean seedlings using a soybean bait (Broders et al, 2007). In Arkansas, a state that is part of the southern soybean cropping area of the United States, Pythium is the only genus of filamentous microorganisms whose isolation frequency increases with flooding (Kirkpatrick et al, 2006). In the present study, Ph.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…helicoides, have been isolated from diseased soybean seedlings using a soybean bait (Broders et al, 2007). In Arkansas, a state that is part of the southern soybean cropping area of the United States, Pythium is the only genus of filamentous microorganisms whose isolation frequency increases with flooding (Kirkpatrick et al, 2006). In the present study, Ph.…”
Section: Discussionmentioning
confidence: 82%
“…For example, Phytophthora sojae is a common plant pathogen that causes root and stem rot worldwide, including pre-emergence damping-off (Schmitthenner, 1999). Several species of Pythium associated with damping-off have also been reported (Kageyama et al, 1982(Kageyama et al, , 2006Naito et al, 1993;Rizvi and Yang, 1996;Broders et al, 2007;Kirkpatrick et al, 2006;Kodama et al, 2010). Fusarium solani, Rhizoctonia solani, and Sclerotium rolfsii also cause damping-off (Killebrew et al, 1993;Naito et al, 1993).…”
mentioning
confidence: 99%
“…Water surplus inhibits germination by causing rapid seed imbibition, embryonic cell membrane rupture, reduction of aerobic respiration, and production of toxic substances (WUEBKER et al, 2001;TIAN et al, 2005;KIRKPATRICK et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…During the vegetative phase, the greatest losses due to water surplus occur at early development stages, when water surplus causes reductions in plant stand (LINKEMER et al, 1998;KIRKPATRICK et al, 2006) and in nitrogen fixation (BACANAMWO & PURCELL, 1999). Water surplus between flowering and early grain filling reduces the number of pods per plant, seeds per pod, and grain productivity (GRIFFIN 1 Bortoluzzi et al & SAXTON, 1988;SCHÖFFEL et al, 2001;RHINE et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bates et al (2008) demonstrated that these species were pathogenic in soybean. In addition, Kirkpatrick et al (2006a) reported that 47% of 208 selected isolates of Pythium spp. were pathogenic to soybean and were moderately to highly aggressive, based on plant emergence and root discoloration.…”
Section: Introductionmentioning
confidence: 99%